Book Review of Why Rural Schools Matter - Daniel Allen (Journal of Research in Rural Education, 2015)
Despite the fact that nearly 51 million students in the United States receive their education in rural communities, rural educational research has suffered from a dearth of publications when compared to research on urban education (Tieken, p. 6). However, Mara Casey Tieken's (2014) contribution, Why Rural Schools Matter, provides an excellent example of scholarship that will lead to greater interest in and understanding of the fi eld of rural education. Specifi cally, this work focuses on the role that rural schools have in determining the relationship between education and race. In the post-integration South, the histories of many communities are tainted by slow and agonizing adherence to the Brown v. Board decision (Tieken, 2014). Furthermore, the African American struggle has had signifi cant effects on the delicate relationship that Whites and Blacks have shared in the post-segregation South. Such rural stories need to be told.